Awareness and attitudes on epilepsy among undergraduate health care students in Southern Brazil - Falavigna,Asdrubal (2009)
OBJECTIVE: To evaluate the awareness on epilepsy among undergraduate health care students in a private university. METHODS: A self-administered questionnaire about epilepsy was applied to 417 students at Universidade de Caxias do Sul. The answers were analyzed in two groups: group 1, medical and nursing students; group 2, psychology, physiotherapy and nutrition students. RESULTS: Most of the students were familiar with the disease. Although many of them recognize brain disease as a cause of seizure, it was observed that a quarter of them linked epilepsy with mental disease. Besides, a relevant portion of the sample presents mistaken attitudes on seizure management. CONCLUSION: There is lack of information on epilepsy among these students. The students and the health care professionals are important vectors of information. Therefore, further discussion on this subject is necessary in health care training to demystify some aspects concerning the disease.